EGSnrc calculation of activity calibration factors for the Vinten ionization chamber. (April 2018) - Townson, R.; Tessier, F.; Galea, R.
Abstract: The National Physical Laboratory Vinten 671 chamber was selected as a proving ground for a new radionuclide source model in the EGSnrc software. The computational Vinten model is validated against measurements of radionuclide artifacts whose activities were determined by absolute methods. The response of the Vinten chamber is first calculated as a function of gamma energy, but more strikingly, an explicit simulation of radionuclide decay was implemented and now permits the direct determination of a calibration factor, including additional effects due to all decay paths of the radionuclide. The Monte Carlo and experimental calibration factors are found to agree at the percent level, in absolute terms. Abstract : Highlights: An EGSnrc model of the Vinten chamber has been created. A radionuclide decay generation scheme has been included in EGSnrc. Preliminary comparison of calibration factors between Monte Carlo and experiment show percent level agreement.